ChemInform Abstract: Copper‐Catalyzed Electrophilic Amination Using N‐Methoxyamines. Issue 44 (13th October 2016) - Fukami, Yutaro; Wada, Takamasa; Meguro, Tatsuhiko; Chida, Noritaka; Sato, Takaaki
Abstract: Copper‐catalyzed electrophilic amination of a triarylboroxin using an N‐methoxyamine to give quick access to a variety of anilines is reported.